On the Formulaic Context of the Aural Experience Vocabulary in Middle English - Błaszkiewicz, Bartłomiej (Uniwersytet Wrocławski. Centrum Interdyscyplinarnych Badań Relacji między Kulturą Oralną i Piśmienniczą, 2019)
The essay is concerned with the most important words encountered in the Middle English dialects which were used to describe the aural sensation and the cognitive impact of the sonic stimuli. The argument traces the way in which this particular lexical group functions in the formulaic, as well as habitual collocative structures in both the alliterative and the rhymed poetry of the English later Middle Ages.The analysis of the particular lexical items seeks to relate the semantic nuance which reflects the medieval cognitive specificity to the patterns of systemic distribution of lexical material in the two distinct poetic traditions which relate in various degree and ways to the legacy of theoral culture which was prevalent at the dawn of the medieval period.
Keywords: aural symbols; formulaic; alliterative; rhyme; Middle English